Diversity Tajdid Dan Konstruksi Islamic Studies - Anshori, Isa (Islam Kontemporer, 2016)
One of the largest religious organization in Indonesia is Muhammadiyah. Movement of religious organizations has attracted many people from various dsiplin science related to the characteristics and the vision of the progress of (modern) in the stretcher, various breakthroughs made by the Islamic organization Muhammadiyah in order to find an alternative solution to the problem of Muslims in Indonesia, especially in relation to Islamic ideology religious and social praxis.This research is the study of literature / literary using the method of philosophical analysis, because of the issues examined are related to epistemological aspects ijtihad and tajdid present in Muhammadiyah religious organizations in Indenesia, the approach taken is patterned historical-thematic.Ijtihad and tajdid that characterizes Muhammadiyah Muhammadiyah is as elan vital, especially at the beginning of its emergence in the nineteenth century AD, where Islam in Indonesia, especially Java suffused with various mythological takhayyul, khurofat and heresy, so that Islam should be a driving force of progress mankind (dynamic and liberating) instead became stagnant religion. Early emergence of Muhammadiyah regarded as a battering ram "theological rigidity" for Indonesian Muslims, who not only clarify theological issues alone but also raises awareness and motorcycle Indonesian independence movement of imprialisme and colonialism.However, in its development, tajdid as elan vital Muhammadiyah, the beginning of the century twenty-one accused by sabagian circles have undergone a process of stagnation and just dwell on the issue of routine administrative organization and institution that has been so great that the function of liberating as the motor of Islamic civilization berkemajuan in Indonesia considered as in its early era of Muhammadiyah. It then pushes the internal Muhammadiyah to critical reflection on the organizations existence. Various critical reflection undertaken by activists and sympathizers Muhammadiyah bring a wide variety of interpretations of tajdid Muhammadiyah so bring diversity in shape, attitude and action.It is undeniable that diversity is influenced by the views of life (world view) respectively in view of the problems (the reality) that exist. World view of each variant that can be tracked in episteme each class. Thus, there are at least two major groups in the body of Muhammadiyah, a group of conservative and progressive groups (contextual), besides that it appeared also a third group, namely, integrative group.The three groups derived from ideology religious same ideals of purification of Islam, but the first two groups are considered to remain and fight the great ideals of Muhammadiyah in social praxis religious (Charity Effort Muhammadiyah or called by AUM), while the latter shifted in integrative group ideology (especially in the Islamic discourse in practical politics).Epistemologically konservatife and progressive groups have a major role in shaping epistemology Islamic movement Muhammadiyah in Indonesia, though often tinged tension between them. In conjunction with the development of Islamic Science, then both together in reconstructing epistemology of science Islam (Islamic Studies), a group of conservative through the process of purification ideology or deconstruction radical and partial (Islamization of Science) like the idea of Syed Muhammad Naquib al-Attas, and groups of progressive use integration M. Amin Abdullah -interkoneksi models, thus the dialectic epistemelogis both groups into a solution for the construction of Islamic scholarship 21st century.